PENGARUH MANAJEMEN PERUBAHAN TERHADAP GAYA KEPEMIMPINAN SERTA DAMPAKNYA PADA MOTIVASI KERJA DAN KINERJA KARYAWAN DI PT BANK TABUNGAN PENSIUNAN NASIONAL PURNA BAKTI CABANG JEMBER - Dian Arifana (RELASI : JURNAL EKONOMI, 2015)
This study aimed to analyze the effect of change management on the leadership styles, change management on work motivation, change managementon employees performance, leadership styles on work motivation, leadership styles on employees performance and work motivation on employees performanceatPT Bank Tabungan Pensiunan Nasional Purna Bakti Branch Jember. This research study is categorized as an explanation (explanatory research) or research causal (causal research), because this study intends to clarify the causal relationship (cause and effect) between variables by testing the hypothesis that has been formulated with samples Simple Random Sampling technique is based on the number of employees Broiler Farms as many as 100  people.The analysis model used in this study is Structural Equation Modeling (SEM). From the results, influence of total change management on the leadership styles of 1.161 with a positive direction, change management on work motivation of 0.359 with a positive direction, change management on employees performance of 0.406 with the positive direction, leadership styles on work motivation of 0.134 with a positive direction, leadership styles on Employees Performance of 0.072 with a positive direction and work motivation on Employees Performance of 0.330 with a positive direction.Based on these tests it can be stated that the change management has the greatest total effect on leadership stylesinPT Bank Tabungan Pensiunan Nasional Purna Bakti Branch Jember.